Development of Validated Methods and Quantification of Curcuminoids and Curcumin Metabolites and Their Pharmacokinetic Study of Oral Administration of Complete Natural Turmeric Formulation (Cureit™) in Human Plasma via UPLC/ESI-Q-TOF-MS Spectrometry - Shintu Jude; Augustine Amalraj; Ajaikumar B. Kunnumakkara; Chandradhara Divya; Bernd-Michael Löffler; Sreeraj Gopi (Molecules, 2018)
Specific and sensitive ultra-high performance liquid chromatography-quadrupole time of flight-mass spectroscopy (UPLC-QTOF-MS) methods have been developed for the determination of curcuminoids and curcumin metabolites in human blood plasma. The UPLC-QTOF-MS method used a binary solvent delivery system and the chromatographic separation was performed on a C-18 (2.1 × 50 mm; 1.7 µm) column. Mass spectra were obtained on a Waters Xevo G2S Q-TOF mass spectrometer. The developed methods to characterize the pharmacokinetics of curcuminoids and curcumin metabolites in human blood plasma after an oral administration of bioavailable curcumin—Cureit™—were validated. It was found that the complete turmeric matrix enhances the concentration of tetrahydrocurcumin (THC), hexahydrocurcumin (HHC), octahydrocurcumin (OHC), curcumin-O-glucuronide (COG) and curcumin-O-sulfate (COS) in the blood plasma once the product is administrated.